Analysis of the 16S rRNA gene for the characterization of the bacterial community of the Lambro river (Italy) - De Lorenzi, Lisa; Carimati, Barbara; Parma, Pietro (Frontiers in Water, 2022)
Characterization of the microbial community of a river can provide various indications, such as its general state of health or the presence of contamination. Furthermore, the study of Bacteroidetes, which have a high degree of host specificity, can provide information on the species involved in any fecal contamination. The analysis of the 16S rRNA was used to characterize the bacterial community of the Lambro river (Italy) through . The results, which were obtained by analyzing water from 15 sampling points, show a reduction in the complexity of the bacterial community as the river enters a densely populated region. The cause could be a source of chemical or physical contamination that carries out a positive selection towards some bacterial species and negative towards others. In addition, a notable increase in the percentage of Bacteroidetes was reported, especially when the river enters regions characterized by high agricultural and livestock activity, such as cattle and pig farming. However, in the samples taken from this area, no Bacteroidetes ascribable to these two species or to the other species considered (i.e., human, dog, and cat) were found. Surprisingly, suspected bacterial contamination of swine origin was identified in a sparsely populated region characterized by small family farms. Finally, the efficient treatment of urban wastewater was confirmed as no markers of fecal pollution of human origin were identified